Clinical practice guidelines for peroral endoscopic myotomy. Issue 5 (6th September 2018) - Inoue, Haruhiro; Shiwaku, Hironari; Iwakiri, Katsuhiko; Onimaru, Manabu; Kobayashi, Yasutoshi; Minami, Hitomi; Sato, Hiroki; Kitano, Seigo; Iwakiri, Ryuichi; Omura, Nobuo; Murakami, Kazunari; Fukami, Norio; et al.
Abstract : Peroral endoscopic myotomy (POEM) is a novel clinical technique developed in Japan used to treat esophageal achalasia and esophageal motility disorders. This technique has been rapidly accepted and widely disseminated throughout our clinical practice because of its low invasiveness, technical novelty, and high efficacy. Since the advent of POEM, there have been no clinical guidelines that clearly indicated its standard of care, and these guidelines have been anticipated both nationally and internationally by clinicians who engage in POEM practice. In 2017, to meet these needs, the Japan Gastroenterological Endoscopy Society (JGES) launched the guideline committee for POEM. Based on the guideline development process proposed by the Medical Information Network Distribution Service (MINDS), the guideline committee initially created research questions on POEM and conducted a systematic review and meta‐analysis on each topic. The clinical research extracted from databases for these clinical questions and the systematic review mainly comprised a few retrospective studies with a small number of participants and short trial periods; hence, the strength of the evidence and recommendations derived from these results was low. Throughout this process, the guideline committee met thrice: once on May 13, 2017, and again on September 17, 2017, to formulate the draft. A consensus meeting was then held on January 14, 2018, in Tokyo to establish the guideline statements and finalize the recommendations using the modified Delphi method. This manuscript presents clinical guidelines regarding current standards of practice and recommendations in terms of the nine chief topics in POEM.